Development of Application-Based Business Models in the Creative Cosplay Industry - Azka Raisa Subagio (Transpublika Publisher, 2025)
The cosplay industry is a rapidly growing sector of the creative economy, combining performing arts, craftsmanship, and digital entrepreneurship. With the rise in global interest in anime, gaming, and pop culture, cosplay has evolved from a recreational activity into a creative industry that generates income for designers, rental providers, photographers, and event organizers. However, the industry still faces major challenges, including high production costs, limited access to quality costumes, and a fragmented service system that hinders business scalability and collaboration. These conditions highlight the urgent need for a more integrated and technology-driven business approach. This study aims to design an application-based business model to address these barriers and optimize opportunities for cosplayers and service providers. A quantitative approach was employed by distributing questionnaires to 112 respondents from various cosplay communities and providers. The collected data were analyzed using descriptive statistics and Business Model Canvas (BMC) mapping to identify key components of the proposed model. Findings show that most respondents express a strong demand for digital platforms that provide affordable access to costumes, efficient rental and purchase services, and community-based features. The results further highlight revenue opportunities for providers and service providers through integrated application systems. This study contributes to the development of digital business models in creative industries and provides practical implications for entrepreneurs and policymakers in supporting innovation within the cosplay sector.